Contribution à l'étude des aptitudes technologiques de souches de Leuconostoc mesenteroïdes - Benyacoub, Nesrine Imene (My University, 2016)
The objective of this work is the characterization of technological properties of four strains of the genus Leuconostocs mésentéroïdes. After a revival on both media MRS and PCA milk at incubation temperatures of 30 ° C, the strains have undergone technological tests such as acidity in the skimmed milk, flavoring, texturing and proteolytic activity and dextran production. Finally, an antibiogram was evaluated on six antibiotics. The results of the evaluation of technological skills indicate that all strains have a good acidifying power. Indeed, after six hours of incubation at 30 ° C, the pH value decreases to 6.33 and the acidity increases to reach 23D °. It also appears that the strains possess a proteolytic and also a texturing power. This later resulted in adextranproduction which differs from strain to strain with a better result recorded by the strain I9 (0.099g). None of the tested strains revealed a flavoring power. Finally, I1, I7 and I9 strainsshowed a sensitivity to the tested antibiotics, whereas, the MNL strain showed a resistance to all antibiotics. Finally, these four Leuconostoc strains could be interesting for dairy industries.
Keywords: درجة الحموضة دیكستران; Leuconostoc mesenteroïdes; pouvoir acidifiant; protéolyse; dextrane; acidifying power; proteolysis